Combined use of GABA and sitagliptin promotes human β-cell proliferation and reduces apoptosis. Issue 2 (February 2021) - Liu, Wenjuan; Lau, Harry Kevin; Son, Dong Ok; Jin, Tianru; Yang, Yehong; Zhang, Zhaoyun; Li, Yiming; Prud'homme, Gerald J; Wang, Qinghua
Abstract : γ-Aminobutyric acid (GABA) and glucagon-like peptide-1 receptor agonist (GLP-1RA) improve rodent β-cell survival and function. In human β-cells, GABA exerts stimulatory effects on proliferation and anti-apoptotic effects, whereas GLP-1RA drugs have only limited effects on proliferation. We previously demonstrated that GABA and sitagliptin (Sita), a dipeptidyl peptidase-4 inhibitor which increases endogenous GLP-1 levels, mediated a synergistic β-cell protective effect in mice islets. However, it remains unclear whether this combination has similar effects on human β-cell. To address this question, we transplanted a suboptimal mass of human islets into immunodeficient NOD-scid-gamma mice with streptozotocin-induced diabetes, and then treated them with GABA, Sita, or both. The oral administration of either GABA or Sita ameliorated blood glucose levels, increased transplanted human β-cell counts and plasma human insulin levels. Importantly, the combined administration of the drugs generated significantly superior results in all these responses, as compared to the monotherapy with either one of them. The proliferation and/or regeneration, improved by the combination, were demonstrated by increased Ki67 +, PDX-1 +, or Nkx6.1 + β-cell numbers. Protection against apoptosis was also significantly improved by the drug combination. The expression level of α-Klotho, a protein with protective and stimulatory effects on β cells, was also augmented. Our study indicates that combined use of GABA and Sita produced greater therapeutic benefits, which are likely due to an enhancement of β-cell proliferation and a decrease in apoptosis.